2008
DOI: 10.1007/s00403-008-0845-2
|View full text |Cite
|
Sign up to set email alerts
|

SERPINE1 (PAI-1) is deposited into keratinocyte migration “trails” and required for optimal monolayer wound repair

Abstract: Cutaneous tissue injury, both in vivo and in vitro, initiates activation of a "wound repair" transcriptional program. One such highly induced gene encodes plasminogen activator inhibitor type-1 (PAI-1, SERPINE1). PAI-1-GFP, expressed as a fusion protein under inducible control of +800 bp of the wound-activated PAI-1 promoter, prominantly "marked" keratinocyte migration trails during the real-time of monolayer scrape-injury repair. Addition of active recombinant PAI-1 to wounded wild-type keratinocyte monolayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 41 publications
5
68
1
Order By: Relevance
“…The study of PAI-1 function in migration is complicated since this molecule influences migration through proteolytic and non-proteolytic functions by interacting with vitronectin and LDL receptor-related protein (LRP) Czekay et al, 2011). In apparent contradiction with our results, recent studies demonstrate that PAI-1 expression is required to induce optimal migration of keratinocytes (Providence and Higgins, 2004;Providence et al, 2008). This discrepancy may be explained by a dose dependent mechanism since some PAI-1 cellular effects are dose dependent (Bajou et al, 2004;Devy et al, 2002).…”
Section: Discussioncontrasting
confidence: 99%
“…The study of PAI-1 function in migration is complicated since this molecule influences migration through proteolytic and non-proteolytic functions by interacting with vitronectin and LDL receptor-related protein (LRP) Czekay et al, 2011). In apparent contradiction with our results, recent studies demonstrate that PAI-1 expression is required to induce optimal migration of keratinocytes (Providence and Higgins, 2004;Providence et al, 2008). This discrepancy may be explained by a dose dependent mechanism since some PAI-1 cellular effects are dose dependent (Bajou et al, 2004;Devy et al, 2002).…”
Section: Discussioncontrasting
confidence: 99%
“…Dysregulated PAI-1 expression is a causative factor in aberrant wound healing and fibrosis. Following injury in vitro, PAI-1 is induced and its expression is restricted to the wound margin where it is required for efficient keratinocyte migration [31,34,50]. Coincidentally, uPA expression is also elevated at the migratory cohort [35].…”
Section: Pai-1 In Physiological and Pathophysiological Cutaneous Wounmentioning
confidence: 99%
“…Treating cells with PAI-1 neutralizing antibody significantly slowed wound repair (Providence, Higgins et al 2008). It has also been reported that PAI-1 controls uPA-mediated cell migration by balancing cell adhesion and detachment activities (Deng, Curriden et al 1996).…”
Section: Negatively Regulates Fibrinolysismentioning
confidence: 86%
“…This is demonstrated by the following observations. PAI-1 is deposited onto the migration trail of keratinocytes during the healing of monolayer wound (Providence, Higgins et al 2008). Addition of active PAI-1 promotes directional migration of both wild type and PAI-1 deficient (PAI-1, -/-) keratinocytes (Providence, Higgins et al 2008).…”
Section: Negatively Regulates Fibrinolysismentioning
confidence: 99%
See 1 more Smart Citation